Risk factors for active tuberculosis in human immunodeficiency virus-infected individuals - Vijay Prakash Turaka; Roshini G Nair; Tunny Sebastian; Rajesh Kannangai; Joy Sarojini Michael; George M Varghese (Wolters Kluwer Medknow Publications, 2019)
Context: Tuberculosis (TB) has become the most common opportunistic infection among individuals with human immunodeficiency virus (HIV) infection worldwide and continues to be a major killer resulting in 0.4 million deaths every year. While some of the risk factors for developing TB in HIV-infected individuals are known, identifying other risk factors will help in screening strategies to pick out those at higher risk for closer follow-up. Aims: The aim of this study was to identify the risk factors related to the development of active TB in HIV-infected individuals. Settings and Design: This case-control study among the HIV-infected individuals was carried out at a HIV clinic in a large tertiary care hospital in South India. Methods: HIV-infected individuals >18 years of age with confirmed TB were chosen as cases. For each case, two age- and sex-matched controls, diagnosed to have HIV infection without active TB or history of TB, were included. The potential risk factors for the development of active TB were evaluated using the odds ratios (ORs) and logistic regression analysis. Results: A total of 150 patients, 50 cases (mean age: 39.3 ± 7.2 years) and 100 controls (mean age: 40.2 ± 7.1 years) were included. On univariate analysis, smoking (OR 8.14, 95% confidence interval [CI]: 3.13-21.21; P < 0.001), low body mass index (OR 6.31, 95% CI: 2.75-14.48; P < 0.001), chronic obstructive pulmonary disease (P = 0.013), ethanol consumption (OR 8.61, 95% CI: 3.57-20.81; P < 0.001), CD4 cell count < 200 cells/μL (OR 13.12, 95% CI: 5.64-30.50; P < 0.001), and not on antiretroviral treatment (ART) (13.34, 95% CI: 5.85-30.41; P < 0.001) were associated with active TB. The risk factors found to be independently associated were CD4 counts < 200 cells/μL (OR 5.75, 95% CI: 1.81-18.20; P = 0003), smoking (OR 7.40, 95% CI: 1.47-37.15; P = 0.015), and not being on ART (OR 13.94, 95% CI: 3.84-50.61; P < 0.001). Conclusion: Initiating ART as soon as possible and patient education on modifiable risk factors including counseling for smoking cessation for HIV-infected individuals are warranted.